Negotiating Uncertainity and Earning Respect: A Qualitative, Longitudinal Study of Young People Ageing Out of State Care in Ireland - Glynn, Natalie (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2020)
This thesis is an exploration of the lived experience of the transition out of care at the age of 18 in Ireland. There is a plethora of research demonstrating the marginalisation and disadvantage experienced by care leavers internationally. Though Ireland's research base is limited, the hardships that care experienced young people face is considered broadly similar to that seen elsewhere. The point of leaving care has been identified as a potentially critical turning point at which services might moderate later outcomes. However, while there is growing evidence identifying social support and identity development as crucial elements, there remains a gap in our understanding of the care-leaving process from the perspective of young people. Initiated in 2015, this research took place during a time of evolving policy and supports for care leavers in the Irish context. Legislation that was passed in 2015 and enacted in 2017 entitles all young people with a history of at least 12 months in care between the ages of 13 and 18 to an aftercare plan identifying their transition needs and available supports. Concurrently, the Child and Family Agency standardised a national policy on financial support for care leavers and initiated the establishment of Aftercare Steering Committees in each service area. These legislative and policy developments expanding and mandating provisions for care leavers form the contextual backdrop for this study. The study utilised a qualitative longitudinal multi-case study methodology underpinned by a critical social constructionist epistemology. Sixteen care leavers from across Ireland, six young women and 10 young men who had aged out of care within the past year, were recruited for a year-long follow-up study. Data were collected at three points in time using in-depth interviewing techniques and supported by creative documentation during the interim period between meetings. The fieldwork was initiated by a community assessment process in which gatekeepers and other stakeholders were contacted. Recruitment was pursued through these contacts and included a variety of services, such as aftercare service providers, homelessness services, teen pregnancy and addiction services. Utilising liminality theory, Recognition theory and the concept of precarity, the analysis revealed a number of insights into the interplay between structure and agency in the transition out of care. The analysis identified two processes in which the care leavers engaged to manage the transition out of care: striving for a 'normal' life and negotiating uncertainty. 'Normal' life adhered to a traditional image of standard adulthood that developed in the 1950s, including financial stability from employment, homeownership and family formation. Ageing out in a context of welfare retrenchment and youth policy that encourages individuals' reliance on family supports, young people described uncertainty about the future and the meeting of their vital needs, such as housing and food. In the system of rationed supports, care leavers sought to create options for themselves and position themselves as deserving of state assistance. Young people's narratives of their experiences with aftercare services and supports underscored the ways in which the concept of the deserving and undeserving poor continue to operate in the Irish child welfare system. Some young people, especially those who were not in education, employment or training, felt misrecognised by the system as undeserving of assistance. Young people contested what constituted deserving, identifying their care experience and their age as markers of deserving-ness, and asserted their moral identities through engagement with or aspiration to valued life activities, such as continuing in education. Relationships proved central to the young people's experiences, both in developing skills to manage them and utilising them for support. As time passed, young people moved from aftercare arranged housing into situations of hidden homelessness, relying on their friends and families for safe housing. Many sought to form new relationships as they entered new social fields, such as higher education and employment. However, several mentioned concerns about how the stigma associated with care experience had the potential to spark pity or judgment in others. In these narratives, the ability to be vulnerable with others arose as a key skill in relationship development, though several noted that care stigma inhibited their ability to be vulnerable with new people. Finally, the analysis highlights the importance of supporting both the material and psycho-social needs of young people as they age out of care. Drawing on these conclusions, the thesis concludes with implications for policy and practice, including the pairing of social investment and social inclusion policies to create a more holistic approach to aftercare policy.
APPROVED
Keywords: Ageing Out; Foster Care; Residential Care; State Care; Kinship Care; Recognition Theory; Liminality; Precarity; Social Investment Policy; Care Leavers